Potencial de risco no trabalho cotidiano de equipes do Serviço de Atendimento Móvel de Urgência - SAMU - Moema Santos Souza (2021)
Urgent and emergency care has grown and become more significant in Brazilian and global society, with emphasis on Mobile Pre-Hospital Care (APH Mobile) for the possibility of early, fast and effective care for victims of various diseases. In Brazil, APH Mobile is carried out by the Mobile Emergency Care Service (SAMU), a component of the urgency and emergency network of the Unified Health System (SUS), called 192. The unpredictability and complexity of care can trigger the occurrence incidents and adverse events (AE) that could be avoided by identifying potential risk. The objectives of this study were to analyze situations with potential risk for users in the daily work of the Mobile Emergency Pre-Hospital Care Service; and, understand the daily work of professionals in the Mobile Emergency Pre-Hospital Care Service, highlighting risk situations that contribute to incidents with users. This is a qualitative study, based on the theoretical framework of Daily Life by Michel de Certeau. Thirty-two SAMU professionals from Belo Horizonte/Minas Gerais/BR (doctors, nurses, nursing technicians and conductors) who work directly in care, and two coordinators, one from the Nucleus of Continuing Education (NEP) and one from nursing participated in the study. Data were collected from July to October 2020, through in-depth interviews with a semi-structured script, carried out online, via a virtual platform. Participants were chosen according to the snowball technique, which consists of choosing the initial participants of a sample that indicate other possible participants, and so on, until data saturation. The interviews were submitted to Thematic Content Analysis, and the MAXQDA® software, version 2020, was used as a resource for data organization. From the analysis, four categories emerged: 1- Organization of the work routine of the SAMU teams; 2 - Adverse situations in user assistance; 3 - Potential for risk in the SAMU's daily work; 4 - Changes in the daily work of SAMU teams in front of Covid-19. The first category revealed that SAMU teams organize their daily work using protocols, rules and routines, when shifting shifts, including organizing the ambulance, checking the materials and medications necessary for care, which constitute strategies to define the organization of the service. In the second category, adverse situations experienced by professionals on a daily basis are described. Due to the dynamic, complex and unpredictable nature of care, situations of violence and the severity of patients, teams often adapt the rules, create and reinvent new ways of doing that are not prescribed in the rules and routines, but which are necessary to ensure assistance to users. The third category presents potential risk situations during the teams' assistance to users, triggering possible incidents that could be reduced/avoided. The fourth category shows the changes that have occurred in the daily work of teams with the Covid-19 pandemic, with the implementation of preventive measures before, during and after the appointments, as well as changes in the lining and cleaning of ambulances to mitigate risks to users. It is concluded that the daily work of teams in the mobile emergency care service is marked by strategies through protocols, standards and routines, but in the face of adverse and challenging situations, professionals create and recreate new ways to practice patient care.